Preclinical evaluation and preliminary clinical study of 68Ga-NODAGA-NM-01 for PET imaging of PD-L1 expression - Lingzhou Zhao; Jiali Gong; Sisi Liao; Wenhua Huang; Jinhua Zhao; Yan Xing (Cancer Imaging, 2025)
Abstract Background Programmed cell death 1/programmed death ligand-1 (PD-L1)-based immune checkpoint blockade is an effective treatment approach for non-small-cell lung cancer (NSCLC). However, immunohistochemistry does not accurately or dynamically reflect PD-L1 expression owing to its spatiotemporal heterogeneity. Herein, we assessed the feasibility of using a 68Ga-labeled anti-PD-L1 nanobody, 68Ga-NODAGA-NM-01, for PET imaging of PD-L1. Methods Micro-PET/CT and biodistribution studies were performed on PD-L1-positive and -negative tumor-bearing mice. Additionally, a preliminary clinical study was performed on two patients with NSCLC. NM-01 was radiolabeled with 68Ga without further purification under mild conditions. Results 68Ga-NODAGA-NM-01 exhibited radiochemical purity (> 98%), high stability in vitro, and rapid blood clearance in vivo. Specific accumulation of 68Ga-NODAGA-NM-01 was observed in PD-L1-positive tumor-bearing mice, with a good tumor-to-background ratio 0.5h post-injection. Furthermore, 68Ga-NODAGA-NM-01 PET/CT imaging was found to be safe with no adverse events and distinct uptake in primary and metastatic lesions of the PD-L1-positive patient, with a higher maximal standardized uptake value than that in lesions of the PD-L1-negative patient 1h post-injection. Conclusions 68Ga-NODAGA-NM-01 can be prepared using a simple method under mild conditions and reflect PD-L1 expression in primary and metastatic lesions. However, our findings need to be confirmed in a large cohort. Trial registration NCT02978196. Registered February 15, 2018.